The Effect of Digitalization on Business Efficiency and Competitiveness in the Era of Global Economy - Ilmi, Haifah; Napitupulu, Dea Okviar Egano; Syahfitri, Ririn (Pusat Riset, Yayasan Cinta Negara Indonesia, 2025)
This study aims to explore the effect of digitalization on operational efficiency and business competitiveness in the era of the global economy. In this study, the analysis was conducted using quantitative methods involving a survey of companies that have implemented digital technology in their operations. The results show that digitalization has a significant influence on improving operational efficiency, with companies that adopt digital technology experiencing reduced operational costs, accelerated business processes, and increased productivity. In addition, digitalization is also proven to strengthen business competitiveness by providing greater access to global markets, increasing product innovation, and strengthening customer relationships. Despite challenges in technology implementation, such as high costs and limited digital skills, the findings of this study show that the benefits of digitalization are far greater. This research contributes to the understanding of how digitalization can improve business efficiency and competitiveness in an increasingly competitive and connected global market. The practical implication of the findings is the importance of companies to adopt digital technology and improve employees' digital skills to remain competitive in the digital era. This study also suggests further research to explore the external factors that drive digitalization.